Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

Development of an ultrasensitive magnetic biosensing platform using SERS and aptamer for the ratio detection of chlorpyrifos in tea - Chenxi Jin; Min Cao; Geqi Li; Jiaqi Wang; Chongyang Qin; Pu Wang; Fei Guo; Dejiang Ni; Zhi Yu; De Zhang; Pei Liang (Food Chemistry, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

A new dipeptide from entomogenous fungus Metapochonia suchlasporia Y9 - Hong-Yan Yang; Jia-Qian Yang; Zhi-Pu Huang; Ke-Tao Zhang; Xin-Yi Chen; Jin-Li Zhao; Yan Wang; Qing Zhao; Xiao-Mei Zhang (Natural Product Research, 2026)

Fine mapping and characterization of the bitter gourd mature fruit-length QTL mfl5.1 reveals a lectin receptor-like kinase gene McLECRK1b controlling fruit elongation - Feifan Chen; Jiajun Wei; Yiwei Wen; Daolong Liao; Jiayu Liu; Xuzhen Li; Kaihong Hu; Jiayu Guo; Shanming Li; Hongyu Pu; Fanyang Jin; Libo Tian; et al. (Theoretical and Applied Genetics, 2026)

Enhanced landslide detection via multi-module deep learning: a morphology-dependent performance analysis approach - Zhengwu Yuan; Sen Kang; Pinglang Kou; Qiang Xu; Xiaobo Luo; Qinchuan Gu; Xinchan Li; Zhao Jin; Chuanhao Pu (Bulletin of Engineering Geology and the Environment, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

Amino acid and appendicular skeletal muscle mass insufficiency are associated to cognitive decline in Chinese population - Ting Tang; Shuxian Zhang; Yanni Pu; Siquan Li; Bin Jiang; Huiting Liang; Kunmu Zheng; Yan Zheng; He Huang; Jin Li; Xiaodong Pan (GeroScience, 2026)

Uncovering the Community Structure and Adaptive Characteristics of Soil Protists Across Natural, Semi‐Natural and Highly Degraded Habitats - Shi‐wei Feng; Xiaonan Wang; Ping Wen; Jing‐li Lu; Zhuo‐hui Wu; Xinzhu Yi; Wen‐sheng Shu; Jie‐Liang Liang; Pu Jia; Jin‐tian Li (Environmental Microbiology, 2026)
Protists are vital to soil ecological functions. However, their diversity and community patterns remain poorly characterised across habitats. This study investigated protists in 270 samples spanning five terrestrial ecosystems: natural (forest, grassland, desert), semi‐natural (farmland) and highly degraded (mine wasteland). The species richness of protists and the consumer functional group were highest in farmland and lowest in mine wasteland. We demonstrated that habitat type ( R partial Mantel = 0.291) exerted stronger effects on protistan communities than geographic distance ( R partial Mantel = 0.072). While α‐diversity drivers varied among habitats (e.g., total phosphorus (TP) was only positive in farmland and forest), β‐diversity was consistent and significantly correlated with mean annual temperature (MAT), mean annual precipitation (MAP), aridity index (AI) and moisture. We identified nine potential ecological groups of protists, reflecting their adaptive differentiation. To explore community assembly, a null model was conducted, revealing that stochastic processes dominated all habitats. Furthermore, co‐occurrence networks of protists, prokaryotes and fungi showed lower modularity and stability in mine wasteland compared with other habitats, indicating co‐occurrence patterns may be more specialised under resource limitation. Collectively, our results highlight the importance of habitat type in shaping protistan communities, suggesting that protists can be predictably regulated in degraded environments.

Chemistry-informed marine copper water quality criteria derived via salinity- and DOC-corrected toxicity modeling - Heng Zhang; Qing-Wei Li; Xin-Ming Pu; Jin-Fen Pan; De-chi Lu (Regional Studies in Marine Science, 2026)

Mechanistic insights into hepatic metabolic disruption induced by combined exposure to pristine and aged polyamide microplastics and triclosan in zebrafish - Qiuhui Qian; Haolei Zhang; Guanchen Cheng; Xingcheng Liu; Ying Zhu; Qian Pu; Jin Yan; Zejun Wang; Yuhuan Zhang; Jieyi Li; Huili Wang (Process Safety and Environmental Protection, 2026)

Ecotoxicity of silver nanoparticles in marine waters: Global gap between exposure and seawater quality criteria - Qing-Wei Li; Heng Zhang; Xin-Ming Pu; Daosen Liu; Jin Li; Romana Manzoor; Jin-Fen Pan (Marine Environmental Research, 2026)

Solid waste dumping differentially impacts soil prokaryotic, fungal, and viral communities: Insights from metagenomics - Rongzhou Jin; Can Chen; Jingru Zhang; Yanying Li; Ye Wu; Feifan Wang; Zhipeng Chen; Ting Huang; Qijie Cheng; Xinlin Yu; Pu Jia (Journal of Environmental Sciences, 2026)

Spin state modulation of Fe single atoms via phosphate functionalization for low-temperature iodine redox - Kairun Bo; Minmei Song; Chuanyang Li; Jikun Li; Yanchen Liu; Hengjian Pu; Fan Kong; Jin Li; Teng Zhai; Hui Xia (Chemical Engineering Journal, 2026)

Highly efficient chromium removal by magnetic nitrogen containing carbon-based composite featuring cross-linking networks - Kaige Gao; Jun Li; Yang Jin; Jiang Pu; Yujing Ma; Tianliang Zhang; Houmin Luo (Journal of Water Process Engineering, 2026)

Mechanism of Chain Rockbursts in Deep Excavations Triggered by Dynamic Disturbance: Insights from Stress Path Controlled Failure - Biao Wang; Ben-Guo He; Xiang-Rui Meng; Hong-Pu Li; Zhao-Tong Jin (Rock Mechanics and Rock Engineering, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Electrical ignition characteristics and combustion emission spectra of continuous-flow ADN-based liquid propellant - Shuo Zhang; Hong-Meng Li; Guo-Xiu Li; Jin-Ze Wu; Zhao-Pu Yao; Tao Zhang (Fuel, 2026)

Machine learning-based global landslide susceptibility analysis: spatiotemporal variability and dominant environmental associations - Pinglang Kou; Haoran Yu; Qiang Xu; Minggao Tang; Zhengwu Yuan; Xu Dong; Huajin Li; Chuanhao Pu; Zhao Jin (Bulletin of Engineering Geology and the Environment, 2026)

Nanozyme-mediated drug ion-exchange strategy ameliorates inflammatory bowel disease by scavenging ROS and reprogramming proinflammatory macrophages - Hongyan Lu; Ying Cheng; Xiangling Pu; Xingtao Zhao; Ruolan Li; Ruiqi Sun; Xiaoman Xie; Mingyue Wu; Shuo Zhang; Qiong Pan; Jin Chai (Chemical Engineering Journal, 2025)

Solar-driven interfacial evaporator based on modified black phosphorus nanosheets for desalination and water purification - Mengnan Qu; Jin Zhang; Jiehui Li; Yuhang Gao; Ying Zhang; Pu Feng; Menglin Zhu; Mengge Cao; Zaiwen Yang; Jinmei He (Desalination, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Genetic analysis and localization of aroma candidate genes for rice - Junjun Guo; Xueyu Yang; Liang Gao; Jin Chen; Liang Zhang; Chunlong Zhang; Bo Zhang; Chuyi Wang; Dandan Li; Juan Li; Shihuang Pu; Jiangli Zhang; et al. (Euphytica, 2025)

In-depth comparative immunotoxicity assessment of pristine and aged PLA microplastics in zebrafish larvae: Bioaccumulation and NF-κB signaling insights - Qiuhui Qian; Lihang Li; Qian Pu; Ji Wu; Li Xu; Ying Cheng; Guanchen Cheng; Jin Yan; Zejun Wang; Xuedong Wang; Huili Wang (Journal of Hazardous Materials, 2025)

Unlocking high-valence nickel ions with highly reversible conversion in nickel-based electrode for asymmetric supercapacitors - Yanchen Liu; Liming Wan; Jin Li; Hengjian Pu; Minghui Gu; Minmei Song; Biao Hu; Chengxu Niu; Teng Zhai; Hui Xia (Chemical Engineering Journal, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Effects of Dietary Carbohydrate Levels on Growth Performance, Antioxidant Capacity, and Hepatointestinal Health in Schizopygopsis younghusbandi - Tao Ye; Mingfei Luo; Zhihong Liao; Wenrui Zhang; Xingyu Gu; Xuanshu He; Haiqi Pu; Xiaomin Li; Benhe Zeng; Jin Niu (Fishes, 2025)
Schizopygopsis younghusbandi is an endemic and ecologically important fish species on the Tibetan Plateau. However, its dietary carbohydrate requirement remains unexplored, limiting the development of cost-effective and physiological-friendly artificial feed. This study investigated the effects of different dietary carbohydrate levels on the growth performance, antioxidant capacity, and hepatointestinal morphology of S.younghusbandi. Six experimental diets were formulated with graded carbohydrate levels of 9% (C9), 12% (C12), 15% (C15), 18% (C18), 21% (C21), and 24% (C24). A total of 720 fish (initial weight 37.49 ± 0.25 g) were randomly allocated to six groups in quadruplicate (30 fish per replicate) and reared in tanks (0.6 m × 0.5 m × 0.4 m) for 8 weeks. Results demonstrated that the diet in the C12 group significantly improved weight gain rate (WGR), specific growth rate (SGR), and feed conversion ratio (FCR) (p

Quantifying high-temperature-induced reproductive growth imbalance in citrus at anthesis: Insights from the CF-ASPM model - Xia Qiu; Feiyu Zhu; Ping Huang; Hongwen Chen; YaLi Li; Changbing Pu; Zongnan Li; Dan Zhong; Chao Xiang; Jin Chen; Si Wang (Computers and Electronics in Agriculture, 2025)

Effects of butane-defatted black soldier fly larvae meal replace dietary fishmeal on growth, antioxidant capacity and intestine health of rainbow trout (Oncorhynchus mykiss) - Xiaomin Li; Yongkang Chen; Zhihong Liao; Xuanqi Chen; Xingyu Gu; Tao Ye; Haiqi Pu; Wenjie Li; Bo Zhu; Wei Zhao; Jin Niu (Aquaculture, 2025)

High-entropy perovskite air electrode with fluorine-induced Electron pair modulation strategy for stable and efficient reversible protonic ceramic cells - Chenghao Yang; Jin Li; Yitong Li; Jing Wang; Ruzhi Wang; Jian Pu; Bo Chi (Chemical Engineering Journal, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

The day-one experiment at SLEGS: systematic measurement of the ( γ , 1n) cross sections on 197 Au and 159 Tb for resolving existing data discrepancies - Zirui Hao; Gongtao Fan; Hongwei Wang; Longxiang Liu; Hanghua Xu; Yue Zhang; Yuxuan Yang; Sheng Jin; Kaijie Chen; Zhicai Li; Pu Jiao; Qiankun Sun; et al. (Science Bulletin, 2025)

Simultaneous detection of citrus internal quality attributes using near-infrared spectroscopy and hyperspectral imaging with multi-task deep learning and instrumental transfer learning - Cheng Li; Chen Jin; Yuanning Zhai; Yuanyuan Pu; Hengnian Qi; Chu Zhang (Food Chemistry, 2025)

Alkaloids of the roots of Lindera glauca (Lauraceae) and their chemophenetics significance - Zhen Peng; Jin-Yu Li; Rui Zhan; Hui-Mei Pu (Biochemical Systematics and Ecology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Functional characterization of chemosensory proteins in three sympatric Tomicus bark beetles feeding on Pinus yunnanensis: Implication for the conservation and divergence of ligand-binding profiles - Lin-Mei Pu; Peng-Fei Wang; Yu-Yue Lu; An-Jin Yang; Li-Li Liu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Inhibition of platelet activation process upon tris (2-chloroethyl) phosphate exposure: Role of PFKP-mediated glycolysis and the pentose phosphate pathway - Ziyuan Li; Pu Chen; Yongfeng Lin; Jingxu Zhang; Jian Ding; Rifat Zubair Ahmed; Xiaoting Jin; Yuxin Zheng (Environmental Pollution, 2025)

A survey on vehicle–drone cooperative delivery operations optimization: Models, methods, and future research directions - Jing Zhou; Jin Yi; Zhenyu Yang; Huayan Pu; Xinyu Li; Jun Luo; Liang Gao (Swarm and Evolutionary Computation, 2025)

Identification, biological characterization of Cladobotryum mycophilum and its control during the fruiting process of Lyophyllum decastes - Taorui Wu; Youlong Chen; Wenxin Zhang; Zijian Pu; Jianhua Li; Yawen Xu; Jianhua Cheng; Lijun Cai; Kaihui Hu; Wensong Jin (Archives of Microbiology, 2025)

Pathogenic analysis of Andinoacara rivulatus skin ulcer disease caused by Klebsiella pneumoniae in China - Xinran Shi; Senting Pu; Yihao Li; Kexin Hao; Yunmeng Shan; Nanlin Jin; Shigen Ye (Aquaculture International, 2025)

Application of multi-angle spaceborne observations in characterizing the long-term particulate organic carbon pollution in China - Yun Hang; Qiang Pu; Qiao Zhu; Xia Meng; Zhihao Jin; Fengchao Liang; Hezhong Tian; Tiantian Li; Tijian Wang; Junji Cao; Qingyan Fu; Sagnik Dey; et al. (Science of The Total Environment, 2025)

Study on organic carbon in medium-low mature shale oil reservoirs rich in type II kerogen: Oxidation behavior, thermal effect, and kinetics - Wanfen Pu; Xing Jin; Yuanyuan Bai; Shuai Zhao; Long He; Yibo Li; Tao Li (Fuel, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Electrical ignition of ADN-based green liquid propellant in constant volume combustion chamber and continuous flow - Jin-Ze Wu; Guo-Xiu Li; Hong-Meng Li; Shuo Zhang; Tao Zhang; Zhao-Pu Yao (Advances in Space Research, 2025)

Species-specific sensitivity to CuO nanoparticles: Establishing seawater quality criteria for Chinese marine ecosystems - De-chi Lu; Qing-Wei Li; Xin-Ming Pu; Heng Zhang; Lei Huang; Zhenguang Yan; Jin-Fen Pan (Science of The Total Environment, 2024)

Ultra-low temperature heating system based on dual-source solar assisted heat pump using compound parabolic concentrator-capillary tube solar collector - Li Wei Yang; Jin Huan Pu; Rong Ji Xu; Tong Yang; Hua Sheng Wang (Energy and Buildings, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Salinity influence correction for zinc ion seawater quality criteria and ecological risk assessment in Chinese seas - Jia-yin Xu; Heng Zhang; Xin-Ming Pu; Qing-wei Li; Jin-Fen Pan; Zhen-Guang Yan (Science of The Total Environment, 2024)

Reductants supplement boost the antitumor efficacy of nanomedicine - Zhiyu Kuang; Danping Wang; Qing Wang; Shengyao Xu; Hezhen Xu; Shiyi Zuo; Yaqiao Li; Hao Zhang; Cuiyun Liu; Xiaohui Pu; Jin Sun; Yuezhou Zhang; et al. (Chemical Engineering Journal, 2024)

Quercetin alleviates kidney damage caused by mercury Chloride: The protective effects of quercetin on autophagy and inflammation were studied based on TRIM32/TLR4/LC3 pathway - Fan Jin; JiaYue Li; Chenyu Zhao; Lixiang Gu; Min Pu; Simin Jiang; Mingming Liang; Ying Zhao; Jianli Shen; Agabuwei Agabuwei; Qin Han; Dan Liao (Toxicon, 2024)

Sedimentology and ichnology of the Xiaxishancun Formation of Qujing, Yunnan: Earliest Devonian marginal-marine environments and ecosystems in South China - Jia-Shu Wang; Li-Jun Zhang; Pu Huang; Lu Liu; Jin-Zhuang Xue (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Mobile measurement background quantification methods for determining local traffic emissions and background source contributions to ammonia - Weiwei Pu; Yingruo Li; Di He; Fan Dong; Jin Wu; Xiangxue Liu; Yulu Qiu; Shuangshuang Ge; Zhiqiang Ma (Atmospheric Environment, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Assessing territorial space conflicts in the coastal zone of Wenzhou, China: A land-sea interaction perspective - De Zhou; Xingyu Zhao; Pu Li; Fengzhi Jin; Siyuan Li; Huan Li; Junfeng Wang (Science of The Total Environment, 2024)

Quantitative Assessment of Ultraviolet-Induced Erythema and Tanning Responses in the Han Chinese Population - Yanyun Ma; Yimei Tan; Yue Hu; Weilin Pu; Jinhua Xu; Li Jin; Jiucun Wang (Phenomics, 2024)
Ultraviolet radiation (UVR) can induce erythema and tanning responses with strong diversity within and between populations, but there were no precise method for evaluating the variation in these responses. In this study, we assessed the time course of ultraviolet (UV)-induced responses based on the erythema index (EI) and melanin index (MI) over 14 consecutive days in a pilot cohort study (N = 31). From safety evaluations, we found that no skin blisters occurred at a UV dosage of 45 mJ/cm 2 , but there were significant skin reactions. Regardless of UV dosage, the measurements and variances of EI peaked on day 1 after UV irradiation, and those of MI peaked on day 7. Dose–response curves, including erythema dose–response (EDR) and melanin dose–response (MDR), could measure UV-induced phenotypes sensitively but more laboriously. As an alternative, we directly represented the UV-induced erythema and tanning responses using the erythema increment (ΔE) and melanin increment (ΔM). We found that ΔE and ΔM at 45 mJ/cm 2 significantly correlated with erythema dose–response (EDR) ( R 2 > 0.9) and melanin dose–response (MDR) ( R 2 > 0.9), respectively. Therefore, ΔE and ΔM on day 1 and day 7 after UV irradiation at a dosage of 45 mJ/cm 2 might be ideal alternative measures for assessing individual erythema and tanning responses. Then, a second cohort (N = 664) was recruited to validate the UV-induced phenotypes, and, as expected, the results of the two cohorts were in agreement. Therefore, we developed a simplified and precise method to quantify the UV-induced erythema response and tanning ability for the Han Chinese population.

Acute/chronic triclosan exposure induces downregulation of m6A-RNA methylation modification via mettl3 suppression and elicits developmental and immune toxicity to zebrafish - Qiuhui Qian; Qian Pu; Xin Li; XingCheng Liu; Anyu Ni; Xiaowen Han; Zejun Wang; Xuedong Wang; Jin Yan; Huili Wang (Chemosphere, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Lin Liu; Yuzhou Xue; Yuxin Li; Yangmei Chen; Xingyu Pan; Yujing Huang; Tingqiao Chen; Judan Zhong; Xinyi Shao; Yihuan Pu; Jin Chen (Human Genetics, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Development of in vitro digestion simulation of gastrointestinal tract to evaluate lipolysis and proteolysis: Comparison of infant model digestion of breast milk and adult model digestion of cow milk - Pu Zhao; Xue Yang; Dan Li; Xinghe Zhang; Wei Wei; Qingzhe Jin; Xingguo Wang (Food Hydrocolloids, 2023)

A gluten degrading probiotic Bacillus subtilis LZU-GM relieve adverse effect of gluten additive food and balances gut microbiota in mice - Aman Khan; Shiqing Li; Huawen Han; Wei-Lin Jin; Zhenmin Ling; Jing Ji; Shazia Iram; Pu Liu; Sa Xiao; El-Sayed Salama; Xiangkai Li (Food Research International, 2023)

The Mechanism of Immobilization of Cd(II) by Phosphate-Solubilizing Bacteria Bacillus sp. B19 - Si-Yi Liu; Qiang Pu; Tian-Jin Mo; Guixiang Peng; Yan Sun; Yulong Zhang; Jinjin Wang; Yongtao Li; Hui-Juan Xu (Water, Air, & Soil Pollution, 2023)

Combustion characteristics and concentration measurement of ADN-based liquid propellant with electrical ignition method in a combustion chamber - Hong-Meng Li; Guo-Xiu Li; Lei Li; Jin-Ze Wu; Zhao-Pu Yao; Tao Zhang (Fuel, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

A facile construction of bifunctional core–shell–shell structured magnetic metal–organic frameworks for detection and removal of tetracycline - Jin Li; Ruihong Yao; Bowen Deng; Zhijian Li; Kai Tuo; Congbin Fan; Gang Liu; Shouzhi Pu (Chemical Engineering Journal, 2023)

Exposure to acute waterborne cadmium caused severe damage on lipid metabolism of freshwater fish, revealed by nuclear lipid droplet deposition in hepatocytes of rare minnow - Xiao-Hong Liu; Xu Pang; Li Jin; De-Yong Pu; Zhi-Jian Wang; Yao-Guang Zhang (Aquatic Toxicology, 2023)

Identification of a suppressor for the wheat stripe rust resistance gene Yr81 in Chinese wheat landrace Dahongpao - Huiling Jin; Haipeng Zhang; Xuyang Zhao; Li Long; Fangnian Guan; Yunpeng Wang; Linyu Huang; Xiaoyue Zhang; Yuqi Wang; Hao Li; Wei Li; Zhien Pu; et al. (Theoretical and Applied Genetics, 2023)

New hydrous phases in the Al2O3-SiO2-H2O system under the mantle transition zone conditions - Baoyun Wang; Jin Liu; Suyu Fu; Pu Xiao; Li Li; Xing Ding; Wansheng Xiao (Science China Earth Sciences, 2023)

Complete genome of Sphingomonas paucimobilis ZJSH1, an endophytic bacterium from Dendrobium officinale with stress resistance and growth promotion potential - Jin Li; Hangtao Wu; Qian Pu; Chu Zhang; Ying Chen; Zhengxin Lin; Xiufang Hu; Ou Li (Archives of Microbiology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Phytostabilization mitigates antibiotic resistance gene enrichment in a copper mine tailings pond - Xinzhu Yi; Ping Wen; Jie-Liang Liang; Pu Jia; Tao-tao Yang; Shi-wei Feng; Bin Liao; Wen-sheng Shu; Jin-tian Li (Journal of Hazardous Materials, 2023)

Synthesis of bifunctional NiFe layered double hydroxides (LDH)/Mo-doped g-C3N4 electrocatalyst for efficient methanol oxidation and seawater splitting - Yufei Du; Yichu Zhang; Xunchi Pu; Xiaoying Fu; Xuan Li; Linqin Bai; Yongjun Chen; Jin Qian (Chemosphere, 2023)

Behavior of Sb and As in the hydrogeochemistry of adjacent karst underground river systems and the responses of such systems to mining activities - Weixiao Chen; Pu Liu; Ying Luo; Bo Li; Jichao Peng; Xuejiao Jin (Science of The Total Environment, 2023)

Effectiveness and degradation pathways of bisphenol A (BPA) initiated by hydroxyl radicals and sulfate radicals in water: Initial reaction sites based on DFT prediction - Qi Han; Mingming Wang; Feiyun Sun; Boping Yu; Zijun Dong; Pu Li; Jingwen Luo; Mu Li; Xingliang Jin; Zhiguang Dai (Environmental Research, 2023)

Application of biochar and compost improved soil properties and enhanced plant growth in a Pb–Zn mine tailings soil - Yizhi Cheng; Xuan Bu; Jing Li; Zhihui Ji; Chenggang Wang; Xiao Xiao; Fenglin Li; Zhuo-hui Wu; Guanxiong Wu; Pu Jia; Jin-tian Li (Environmental Science and Pollution Research, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Exogenous Ca2+ Associated with Melatonin Alleviates Drought-Induced Damage in the Woody Tree Dalbergia odorifera - El-Hadji Malick Cisse; Li-Jia Zhang; Yu-Jin Pu; Ling-Feng Miao; Da-Dong Li; Juan Zhang; Fan Yang (Journal of Plant Growth Regulation, 2022)

Efficacy of Bactericides Against Potato Common Scab Caused by Streptomyces in Yunnan, China - Jin Pu; Zhenhua Zhang; Hongji Zhang; Ya Xu; Baoju Zhang; Mengping Yang; Kuixiu Li; Li Zhang; Shen Xiong; Naiqin Zhong; Decai Yu (American Journal of Potato Research, 2022)

Remarkable effects of microbial factors on soil phosphorus bioavailability: A country‐scale study - Jing‐li Lu; Pu Jia; Shi‐wei Feng; Yu‐tao Wang; Jin Zheng; Shu‐ning Ou; Zhuo‐hui Wu; Bin Liao; Wen‐sheng Shu; Jie‐Liang Liang; Jin‐tian Li (Global Change Biology, 2022)
Low soil phosphorus (P) bioavailability causes the widespread occurrence of P‐limited terrestrial ecosystems around the globe. Exploring the factors influencing soil P bioavailability at large spatial scales is critical for managing these ecosystems. However, previous studies have mostly focused on abiotic factors. In this study, we explored the effects of microbial factors on soil P bioavailability of terrestrial ecosystems using a country‐scale sampling effort. Our results showed that soil microbial biomass carbon (MBC) and acid phosphatase were important predictors of soil P bioavailability of agro‐ and natural ecosystems across China although they appeared less important than total soil P. The two microbial factors had a positive effect on soil P bioavailability of both ecosystem types and were able to mediate the effects of several abiotic factors (e.g., mean annual temperature). Meanwhile, we revealed that soil phytase could affect soil P bioavailability at the country scale via ways similar to those of soil MBC and acid phosphatase, a pattern being more pronounced in agroecosystems than in natural ecosystems. Moreover, we obtained evidence for the positive effects of microbial genes encoding these enzymes on soil P bioavailability at the country scale although their effect sizes varied between the two ecosystem types. Taken together, this study demonstrated the remarkable effects of microbial factors on soil P bioavailability at a large spatial scale, highlighting the importance to consider microbial factors in managing the widespread P‐limited terrestrial ecosystems.

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment - Shao‐peng Li; Pu Jia; Shu‐ya Fan; Yingtong Wu; Xiang Liu; Yani Meng; Yue Li; Wen‐sheng Shu; Jin‐tian Li; Lin Jiang (Ecology Letters, 2022)
Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species’ functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment.

Potato Tuber Growth and Yield Under Red and Blue LEDs in Plant Factories - Wei He; Min Pu; Jin Li; Zhi-Gang Xu; Lijun Gan (Journal of Plant Growth Regulation, 2022)

Coupling exogenous melatonin with Ca2+ alleviated chilling stress in Dalbergia odorifera T. Chen - Yu-Jin Pu; El Hadji Malick Cisse; Li-Jia Zhang; Ling-Feng Miao; Mohsin Nawaz; Fan Yang (Trees, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Analysis of saponins detoxification genes in Ilyonectria mors-panacis G3B inducing root rot of Panax notoginseng by RNA-Seq - Guohong Zeng; Jin Li; Yuxiu Ma; Qian Pu; Tian Xiao; Ruihuan Yang; Xiufang Hu (Archives of Microbiology, 2021)
Saponins are kinds of antifungal compounds produced by Panax notoginseng to resist invasion by pathogens. Ilyonectria mors-panacis G3B was the dominant pathogen inducing root rot of P. notoginseng , and the abilities to detoxify saponins were the key to infect P. notoginseng successfully. To research the molecular mechanisms of detoxifying saponins in I. mors-panacis G3B, we used high-throughput RNA-Seq to identify 557 and 1519 differential expression genes (DEGs) in I. mors-panacis G3B with saponins treatments for 4H (Hours) and 12H (Hours) compared with no saponins treatments, respectively. Among these DEGs, we found 93 genes which were simultaneously highly expressed in I. mors-panacis G3B with saponins treatments for 4H and 12H, they mainly belong to genes encoding transporters, glycoside hydrolases, oxidation–reduction enzymes, transcription factors and so on. In addition, there were 21 putative PHI (Pathogen–Host Interaction) genes out of those 93 up-regulated genes. In this report, we analyzed virulence-associated genes in I. mors-panacis G3B which may be related to detoxifying saponins to infect P. notoginseng successfully. They provided an excellent starting point for in-depth study on pathogenicity of I. mors-panacis G3B and developed appropriate root rot disease management strategies in the future.

Two new species of Amanita section Roanokenses with a radicating basal bulb - Juan Zhong; Gui-Wu Li; Jin-Bao Pu; Zuo-Hong Chen; Ping Zhang (Mycological Progress, 2021)

Investigation of eluted characteristics of fulvic acids using differential spectroscopy combined with Gaussian deconvolution and spectral indices - Tingting Li; Fanhao Song; Jin Zhang; Shasha Liu; Weiying Feng; Lingling Zuo; Jia Pu; Baoshan Xing; John P. Giesy; Yingchen Bai (Environmental Science and Pollution Research, 2020)

Contrasting soil fungal communities at different habitats in a revegetated copper mine wasteland - Jie-liang Liang; Jun Liu; Tao-tao Yang; Pan-deng Wang; Sheng-chang Zhang; Pu Jia; Bin Liao; Wen-sheng Shu; Jin-tian Li (Soil Ecology Letters, 2020)

Enhancing nitrogen removal from wastewater in sequencing batch reactors (SBRs) using additional carbon source produced from food waste acidogenic fermentation at different temperatures - Yunhui Pu; Jialing Tang; Xiaochang C. Wang; Yisong Hu; Jin Huang; Shengwang Pan; Yuyou Li (Environmental Science and Pollution Research, 2019)

Root order and initial moisture status influenced root decomposition in a subtropical tree species Liquidambar formosana - Peng Wang; Xiaoxue Liu; Pu Mou; Jin Guo; Shuo Li (Plant and Soil, 2019)

Intracellular Metabolic Changes of Rhodococcus sp. LH During the Biodegradation of Diesel Oil - Ze Chen; Zhou Zheng; Feng-Lian Wang; Yuan-Pu Niu; Jin-Lai Miao; Hao Li (Marine Biotechnology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Outcomes of EC-MPS combined with low-dose tacrolimus in DCD kidney transplantation for high-risk DGF recipients - Li-zi Jiao; Chen-guang Ding; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; He-li Xiang; Xiao-hui Tian; Yang Li; Jin Zheng; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2018)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Effects of a bacterial consortium from acid mine drainage on cadmium phytoextraction and indigenous soil microbial community - Jin-tian Li; Zhi-wei Liang; Pu Jia; Jun Liu; Yi-juan Xu; Yong-jian Chen; Hao-yue Shu; Jia-liang Kuang; Bin Liao; Wen-sheng Shu (Plant and Soil, 2017)

A population association study of vitamin D receptor gene polymorphisms and haplotypes with the risk of systemic lupus erythematosus in a Chinese population - Xu-E Chen; Pu Chen; Shan-Shan Chen; Jin Lu; Ting Ma; Guang Shi; Ya Zhou; Ji Li; Liang Sheng (Immunologic Research, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Nicotine Inhibits Microglial Proliferation and Is Neuroprotective in Global Ischemia Rats - Yan-Zhong Guan; Xiu-Dong Jin; Li-Xin Guan; Hua-Cheng Yan; Pu Wang; Zhi Gong; Shu-Ji Li; Xiong Cao; Yan-Li Xing; Tian-Ming Gao (Molecular Neurobiology, 2015)

The operating performance of a biotrickling filter with Lysinibacillus fusiformis for the removal of high-loading gaseous chlorobenzene - Zhao-Xia Li; Bai-Ren Yang; Jian-Xiang Jin; Yi-Chen Pu; Cheng Ding (Biotechnology Letters, 2014)

Characterization of AvaR1, an autoregulator receptor that negatively controls avermectins production in a high avermectin-producing strain - Jian-Bo Wang; Feng Zhang; Jin-Yue Pu; Juan Zhao; Qun-Fei Zhao; Gong-Li Tang (Biotechnology Letters, 2014)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Improved methods for basic molecular manipulation of the red alga Porphyra umbilicalis (Rhodophyta: Bangiales) - Li-En Yang; Qiu-Ping Jin; Yu Xiao; Pu Xu; Shan Lu (Journal of Applied Phycology, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)